Sistem Pakar Untuk Diagnosa Retardasi Mental Anak dengan Metode Bayes Berbasis Web - Eliya Yuliana; Iqbal Kamil Siregar; Endra Saputra (Building of Informatics, Technology and Science (BITS), 2022)
In children's mental retardation, sometimes the child's parents cannot directly consult with a psychiatric specialist because of the limited time in carrying out activities in the hospital and the high cost. Advances in expert systems can overcome this problem, namely by designing a web-based computer system that is integrated with databases and programming languages ​​such as PHP-MySQL so that it can help patients with mental retardation to diagnose the disorder. The purpose of this research is to build a web-based expert system for diagnosing mental disorders. The application of the expert system in this decision making uses the Bayes method, in probability theory and statistics, the Bayes theorem is a theorem with two different interpretations. In Bayes' interpretation, this theorem states how far the degree of subjective belief must change rationally when there are new clues. to get a diagnosis. The result of the implementation of the system is that the system provides choices in the form of symptoms that must be answered by the patient's parents based on the symptoms experienced by the patient and the results of the process the system will provide information on the mental retardation he experienced in order to get a solution with the handler